Simulations and experiments of the growth of the "tent" perturbation in NIF ignition implosions. (May 2016) - Hammel, B A; Tommasini, R; Clark, D S; Field, J; Stadermann, M; Weber, C
Abstract: NIF capsules are supported in the hohlraum by two thin (∼15-110 nm) Formvar films ("tent"). Highly resolved HYDRA simulations indicate that a large (∼40% peak-average) areal density (ρR) perturbation develops on the capsule during acceleration as a consequence of this support geometry. This perturbation results in a jet of dense DT and, in some cases, CH that penetrates and cools the hot spot, significantly degrading the neutron yield (∼10-20% of 1D yield). We examine "low-foot" and "high-foot" pulse shapes, tent thicknesses, and geometries. Simulations indicate that thinner tents result in a smaller pR perturbation, however, the departure angle of the tent from the capsule surface is important, with steeper angles resulting in larger perturbations.